2018
DOI: 10.1002/smll.201703667
|View full text |Cite
|
Sign up to set email alerts
|

Pseudohalide‐Induced 2D (CH3NH3)2PbI2(SCN)2 Perovskite for Ternary Resistive Memory with High Performance

Abstract: Recently, organic-inorganic hybrid perovskites (OIHP) are studied in memory devices, but ternary resistive memory with three states based on OIHP is not achieved yet. In this work, ternary resistive memory based on hybrid perovskite is achieved with a high device yield (75%), much higher than most organic ternary resistive memories. The pseudohalide-induced 2D (CH NH ) PbI (SCN) perovskite thin film is prepared by using a one-step solution method and fabricated into Al/perovskite film/indium-tin oxide (glass s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(52 citation statements)
references
References 88 publications
0
52
0
Order By: Relevance
“…For each device area, the I LRS and I HRS were measured on six devices in the same batch. As shown in Figure a, both average values of I LRS and I HRS do not change obviously with an increasing device area, clearly opposite to the interface‐based switching mechanism, where the current or resistance is dependent on the device area due to the interface modulation . Therefore, we attributed the creation and annihilation of CF as the main mechanism contributing to the RS operations in this work.…”
mentioning
confidence: 73%
“…For each device area, the I LRS and I HRS were measured on six devices in the same batch. As shown in Figure a, both average values of I LRS and I HRS do not change obviously with an increasing device area, clearly opposite to the interface‐based switching mechanism, where the current or resistance is dependent on the device area due to the interface modulation . Therefore, we attributed the creation and annihilation of CF as the main mechanism contributing to the RS operations in this work.…”
mentioning
confidence: 73%
“…Up to now, the highest reported efficiency of a perovskite solar cell was recorded at 22.7% by the National Renewable Energy Laboratory (NREL) [ 12 ]. The material used was an inorganic-organic hybrid material with a perovskite (ABX 3 ) structure (A: methylammonium (CH 3 NH 3 + , MA), formamidinium (HC(NH 2 ) 2 + , FA), Cs, Rb; B = Pb, Sn; X = halogen anion (Cl, Br and I), (SCN − )) [ 13 , 14 , 15 , 16 , 17 ]. Despite rapid developments in the performance of perovskite solar cells, there have been concerns about several issues such as the photocurrent hysteresis, device stability, and scaling issues that are able to affect the measurement accuracy and/or practical applications of these devices.…”
Section: Introductionmentioning
confidence: 99%
“…For example, 2D OHPs can be obtained by substitution with a pseudohalide such as thiocyanate (SCN−) . Cheng et al demonstrated that 2D OHPs were able to show ternary RS using MA 2 PbI 2 (SCN) 2 . The 2D MA 2 PbI 2 (SCN) 2 was prepared by a spin‐coating method (Figure A).…”
Section: Memristors Based On Ohpsmentioning
confidence: 99%
“…C, Typical I ‐ V curve of the ITO/MA 2 PbI 2 (SCN) 2 /Al memristor. D, The endurance and E, retention characteristics of the memristor…”
Section: Memristors Based On Ohpsmentioning
confidence: 99%